Novel method of fabricating hydroxyapatite incorporated 5-fluorouracil loaded poly (lactide-co-glycolide) microspheres - Lin, Julian Yuting. (2009)
Hydroxyapatite-incorporated PLGA-based microspheres loaded with 5-FU were prepared using the emulsification/solvent evaporation technique. The effects of hydroxyapatite-to-polymer ratio, dimethyl sulfoxide-to-dichloromethane ratio as well the effects of polymer inherent viscosity on encapsulation efficiency were investigated. The drug release rate was studied for 5 weeks in vitro in phosphate buffered solution of pH 7.4 at 37oC. Results showed that higher drug encapsulation was attained at higher hydroxyapatite-to-polymer ratio of 0.1, lower dimethyl sulfoxide-to-dichloromethane ratio of 0.05 and using a polymer with higher inherent viscosity of 0.68 dL/g. The release of drug followed a biphasic pattern with an initial burst within 4 hours of immersion in phosphate buffered saline, followed by a zero order release. Results also indicated that initial bursts could be limited to 6% with high hydroxyapatite-to-polymer ratio of 0.1. However, the presence of hydroxyapatite increased the internal porosity of the microspheres thus increasing the rate of drug release to 1.11 %/day as compared to 0.48 %/day in microspheres without hydroxyapatite.